Pembuatan Buku Panduan Pemanfaatan Taman Bacaan Masyarakat di Perpustakaan Rumah Gadang Kota Padang - Eldys, Donna; Nurizzati, Nurizzati (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract The reading house of the Rumah Gadang community has approximately 4000 copies of books consisting of children's reading, children's stories, fairy tales, and novels, then teen and adult readings, namely novels, poems, short stories, comics, magazines, religious books, books of thought and philosophy . Community reading garden of the Gadang House located in Kampung Batu. The Rumah Gadang community reading park has three services, namely (1) book lending services, (2) talent and potential guidance services for children, (3) Collaborative Activity Services with Various Parties (Partnerships), The main stage of developing a guidebook with the design of several contents in the product that is. The design of components such as the contents of the product there are several elements that I will use to make the guidebook as follows: (1) getting to know the library, the author will discuss at a glance about the Rumah Gadang library, library vision and mission, organizational structure, room layout and service in the library. (2) developing interest and reading habits, here the author will discuss the notion of reading interest and the benefits of reading. (3) Developing reading interests and habits, where the author discusses development in terms of reading and problems with interest in reading. The stages of making guidebooks (1) collecting data and information (2) compiling the writing framework (3) cover ( 4) preface (5) table of contents (6) Main Content of the Book.Keywords: guidebook, interest in reading